2017
DOI: 10.1111/imj.13375
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial screening and management of young people aged 18–25 years with diabetes

Abstract: Abstract:Background: Routine psychosocial screening and management of people with diabetes is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
4
24
0
2
Order By: Relevance
“…In line with the findings of a systematic review that showed no benefit of patient‐held records, we found no association between the PAID scale total score and use of a diabetes passport. As in our study, other studies found that suboptimal glycaemic control was weakly associated with higher PAID scale total scores . In addition, close associations between depressive symptoms and diabetes distress have been reported previously and discussed intensively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with the findings of a systematic review that showed no benefit of patient‐held records, we found no association between the PAID scale total score and use of a diabetes passport. As in our study, other studies found that suboptimal glycaemic control was weakly associated with higher PAID scale total scores . In addition, close associations between depressive symptoms and diabetes distress have been reported previously and discussed intensively.…”
Section: Discussionsupporting
confidence: 91%
“…The diabetes distress prevalence in the analysed samples of 18–27‐year‐olds (12–16%) was lower than that commonly observed in older adults with later onset . We suspect that the Type 1 diabetes onset early in childhood partly explains the difference.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…1,8,10 It shows the vulnerability of this group and the need to screen for and address mental wellbeing at clinic visits. A total of 19.4% indicated severe diabetes-related stress on the PAID-20 score, 11% were identified as likely having depression and PHQ-4 identified 25.8 and 16.1% with anxiety and depression respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5 Transition programmes have resulted in improvement of diabetes care for young adults with type 1 DM with higher clinic attendance, reduction in admissions with diabetic ketoacidosis (DKA) and a fall in HbA1c. 10 With this study, we aim to investigate young adults aged 18-25 years at a large tertiary diabetes clinic and report physical and psychosocial baseline characteristics of this group. 8 Identifying the mental health burden is important to provide a comprehensive health service and diabetes guidelines recommend routine psychological assessment and treatment.…”
Section: Introductionmentioning
confidence: 99%